Retrofit of the Concrete Structures by CFRP Sheets against Explosion (Journal of Civil Engineering Researchers, 2020)
This paper first offers information on blast wave and blast loading. Then, the dynamic analysis of a single concreteslab against blast loading was conducted by the ABAQUS software program. Maximum stress in CFRP plates inthe center of the reinforced concrete slab was observed in all loading phases, since this area was in the maximumstress zone. It is also an efficient method of retrofitting the slabs against blast loading using externally fiberreinforcedpolymer attached to the tensile side of the slab. © 2017 Journals-Researchers.
Keywords: Blast load; reinforced concrete slab; CFRP; retrofitting